A monolithic gold nanoparticle@metal-organic framework composite as CO2 photoreduction catalyst. (March 2023) - Tian, T.; Xu, J.; Abdolazizi, A.; Ji, C.; Hou, J.; Riley, D.J.; Yan, C.; Ryan, M.P.; Xie, F.; Petit, C.
Abstract: The application of metal-organic frameworks (MOFs), especially MOF composites, has been hindered by a lack of method to process powders into useable forms. To address this challenge, we report here a low temperature synthesis method that enables direct formation of a densified monolithic MOF composite, i.e. Au@ZIF-67. The monolithic composite contains Au nanoparticles (Au NPs) that are well-dispersed and encapsulated within ZIF-67 particles. It exhibits high surface area, bulk density, and mechanical robustness as observed in monolithic ZIF-67, while retaining the localized surface plasmonic resonance (LSPR) characteristic of Au NPs. Benefiting from this unique combination, the monolithic Au@ZIF-67 samples display an enhanced CO2 photoreduction performance under visible light—with the best-performing Au@ZIF-67 sample showing a volumetric CO production rate 1.5 and 3 times higher compared to the pristine monolithic ZIF-67 and ZIF-67 powder, respectively. Graphical abstract: Image 1 Highlights: We have synthesized the first core-shell monolithic MOF composite, Au@ZIF-67, by a sol-gel method. The composite presented an improved volumetric CO2 photoreduction efficiency compared to the pristine monolithic ZIF-67 and ZIF-67 powder. The improved performance is attributed to the high bulk density (monolith), the plasmonic effect (Au), and the heterojunction formed between Au and ZIF-67.